Circ_0060927 regulates miR-331-3p/ERK/MAPK pathway reaction in non-small cell lung cancer through METTL14-driven methylation - Liao, Yang; Song, Ji; Luo, Chun; Xiang, Jin; Cheng, Sheng (Frontiers in Oncology, 2025)
BackgroundNon-coding RNA is one of the most paramount genetic regulators. circRNAs (Circular RNAs) are a potential modulator of various tumors, especially in non-small cell lung cancer (NSCLC). This study focused on elucidating the underlying influence of circ_0060927 on NSCLC progression and relevant regulatory mechanisms.MethodsManipulating circ_0060927, MAP2K7, and METTL14 expression in NSCLC cells by lentiviral vectors. The expression of MAP2K7, ERK, p-ERK, p38MAPK, and p-p38MAPK was measured by RT-qPCR and Western Blot experiments. RIP-RT-qPCR was performed to quantify the m6A methylation status of circ_0060927. Cell Counting Kit-8, cell apoptosis assay, wound healing assay, and transwell assay were employed to identify the discrepancy of tumor cells’ malignant phenotypes, including cell proliferation, cell motility, and apoptosis.ResultsL78 and A549 cells showed high expression of circ_0060927 and its 6A methylation level compared to normal lung epithelial cells. Circ_0060927 could promote tumor cells’ proliferation and motility, and reduce cell apoptosis. These effects depended on the m6A methylation derived from METTL14. Besides, circ_0060927 combined miR-331-3p specifically in NSCLC cells to repress its function; simultaneously, miR-331-3p impeded NSCLC cells through suppressing the ERK/MAPK pathway activation by interfering with the expression of MAP2K7 protein.ConclusionsCirc_0060927 positively regulates NSCLC cells’ malignant biological behaviors via targeted binding to miR-331-3p. MiR-331-3p could be recognized as a promising inhibitor for the ERK/MAPK signal pathway in NSCLC cells since it has an interfering effect on MAP2K7 protein. These results cast a meaningful insight into the shadow regarding molecular mechanisms underlying NSCLC and the potential therapeutic perspective of circRNA methylation.